A moderated mediation examination of proactive personality on employee creativity: A person-environment fit perspective. Issue 3 (11th May 2015) - Jiang, Wan; Gu, Qinxuan
Abstract : Purpose: – By integrating proactive perspective and person-environment fit (P-E fit) perspective, this study intends to examine a moderated mediation model of proactive personality to investigate its effects on employee creativity. The current study proposes felt responsibility for change mediates the relationship between proactive personality and employee creativity. The purpose of this paper is to identify core self-evaluation (CSE) and developmental feedback received as personal and situational moderators on the relationship between proactive personality and felt responsibility for change. Design/methodology/approach: – A matched sample from 232 employees and their supervisors of software companies in China was used to test the hypotheses. Hierarchical regression analyses and moderated mediation approach were conducted to examine the proposed model. Findings: – The results indicate that felt responsibility for change mediates the positive relationship between proactive personality and employee creativity. CSE and developmental feedback received positively moderate the relationship between proactive personality and felt responsibility for change. In addition, CSE and developmental feedback received are two moderators in the path from proactive personality to employee creativity via felt responsibility for change such as the indirect relationship between proactive personality and employee creativity through felt responsibility for change is more pronounced when CSE and developmental feedback received are higher rather than lower, respectively. Research limitations/implications: – The paper contributes to creativity literature by identifying felt responsibility for change as the mediator on the relationship between proactive personality and employee creativity. The current study also contributes to proactive perspective and P-E fit theory by investigating the moderating roles of CSE and developmental feedback received on the relationship between proactive personality and felt responsibility for change. Although data were collected from multiple sources to avoid common method variance, the cross-sectional design cannot unequivocally examine the direction of causality in this study. Originality/value: – By examining both mediating and moderating effects, the paper contributes to uncovering the black box in which employees with proactive personality exhibit felt responsibility for change and creativity.